Alopecia areata: Animal models illuminate autoimmune pathogenesis and novel immunotherapeutic strategies. - Gilhar, A; Schrum, A; Etzioni, A; Waldmann, H; Paus, R (Elsevier, 2016)
One of the most common human autoimmune diseases, alopecia areata (AA), is characterized by sudden, often persisting and psychologically devastating hair loss. Animal models have helped greatly to elucidate critical cellular and molecular immune pathways in AA. The two most prominent ones are inbred C3H/HeJ mice which develop an AA-like hair phenotype spontaneously or after experimental induction, and healthy human scalp skin xenotransplanted onto SCID mice, in which a phenocopy of human AA is induced by injecting IL-2-stimulated PBMCs enriched for CD56+/NKG2D+ cells intradermally. The current review critically examines the pros and cons of the available AA animal models and how they have shaped our understanding of AA pathobiology, and the development of new therapeutic strategies. AA is thought to arise when the hair follicle's (HF) natural immune privilege (IP) collapses, inducing ectopic MHC class I expression in the HF epithelium and autoantigen presentation to autoreactive CD8+ T cells. In common with other autoimmune diseases, upregulation of IFN-γ and IL-15 is critically implicated in AA pathogenesis, as are NKG2D and its ligands, MICA, and ULBP3. The C3H/HeJ mouse model was used to identify key immune cell and molecular principles in murine AA, and proof-of-principle that Janus kinase (JAK) inhibitors are suitable agents for AA management in vivo, since both IFN-γ and IL-15 signal via the JAK pathway. Instead, the humanized mouse model of AA has been used to demonstrate the previously hypothesized key role of CD8+ T cells and NKG2D+ cells in AA pathogenesis and to discover human-specific pharmacologic targets like the potassium channel Kv1.3, and to show that the PDE4 inhibitor, apremilast, inhibits AA development in human skin. As such, AA provides a model disease, in which to contemplate general challenges, opportunities, and limitations one faces when selecting appropriate animal models in preclinical research for human autoimmune diseases.